2018
DOI: 10.1002/lt.25312
|View full text |Cite
|
Sign up to set email alerts
|

Liver Grafts From Donors After Circulatory Death on Regional Perfusion With Extended Warm Ischemia Compared With Donors After Brain Death

Abstract: Donation after circulatory death (DCD) in Italy constitutes a relatively unique population because of the requirement of a no-touch period of 20 minutes. The first aim of this study was to compare liver transplantations from donors who were maintained on normothermic regional perfusion after circulatory death and suffered extended warm ischemia (DCD group, n = 20) with those from donors who were maintained on extracorporeal membrane oxygenation (ECMO) and succumbed to brain death (ECMO group, n = 17) and those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
112
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 34 publications
11
112
0
Order By: Relevance
“…A total of 16 out of 25 studies reported selection criteria for DCD liver grafts during NRP. (55)(56)(57)(58)(59)(61)(62)(63)65,(67)(68)(69)(70)(72)(73)(74) Graft survival ranged from 42.9% to 100%, and follow-up ranged from 3 to 32 months.…”
Section: Is Nrp Indicated In Both Type 2 and Type 3 Dcd?mentioning
confidence: 99%
“…A total of 16 out of 25 studies reported selection criteria for DCD liver grafts during NRP. (55)(56)(57)(58)(59)(61)(62)(63)65,(67)(68)(69)(70)(72)(73)(74) Graft survival ranged from 42.9% to 100%, and follow-up ranged from 3 to 32 months.…”
Section: Is Nrp Indicated In Both Type 2 and Type 3 Dcd?mentioning
confidence: 99%
“…A study from Italy investigated outcomes in 20 DCD donors that underwent NRP. 75 In Italy DCD donors experienced a prolonged DWIT as a 20-minute no-touch period is required following circulatory arrest. PNF was seen in two patients (10%), IC was seen in two patients (10%), and 1-year graft and patient survival were 85 and 95%, respectively.…”
Section: Normothermic Regional Perfusionmentioning
confidence: 99%
“…According to differences in postoperative liver function and patient recovery, grafts are divided into three categories: early allograft dysfunction (EAD), primary non-function (PNF) and optimal graft function (OG). Lower quality liver allografts are associated with severe ischemia reperfusion injury (IRI), resulting in the occurrence of EAD or PNF, which significantly affect patient survival and allograft survival (1, 2). The incidence of EAD is up to 39.5% in patients with allografts from DCD donors (1).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of EAD is up to 39.5% in patients with allografts from DCD donors (1). A high rate of PNF (10%) and retransplantation (15%) in liver transplant patients was reported in a transplant center in Italy (2).…”
Section: Introductionmentioning
confidence: 99%